2020
DOI: 10.1038/s41598-020-77334-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of BCG vaccination in goat herds with a high prevalence of tuberculosis

Abstract: Vaccination of goats against tuberculosis (TB) has been promoted as an ancillary tool for controlling the disease in infected livestock herds. A three-year trial to assess the efficacy of BCG vaccine was carried out in five goat herds. At the beginning of the trial (month 0), all animals were tested for TB using thee different diagnostic tests. Animals negative to all tests were vaccinated with BCG and all replacement goat kids were also systematically vaccinated throughout the trial. All animals were tested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…This is similar to what has been observed in calves vaccinated with BCG at two to four weeks of age, and revaccinated at two years of age, and then challenged with M. bovis six months after the second vaccination, whereas single-dose vaccinated animals were not protected [12]. Besides, a field trial in BCG-vaccinated goats has shown an increase in TB incidence one year after vaccination [17], suggesting a loss of protective immunity of BCG after this period of time and the need for a revaccination strategy.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to what has been observed in calves vaccinated with BCG at two to four weeks of age, and revaccinated at two years of age, and then challenged with M. bovis six months after the second vaccination, whereas single-dose vaccinated animals were not protected [12]. Besides, a field trial in BCG-vaccinated goats has shown an increase in TB incidence one year after vaccination [17], suggesting a loss of protective immunity of BCG after this period of time and the need for a revaccination strategy.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, most of the vaccinated calves generated strong IFNγ responses to ESAT-6-/CFP-10-specific antigens after about 6 months of exposure. In agreement with this observation, BCG-vaccinated goats became infected in less than a year of exposure to infected goats in Spain (49). Thus, these observations could suggest that the DoI of BCG is <1 year requiring a boosting dose.…”
Section: Discussionsupporting
confidence: 80%
“…The role of the humoral immune response against bTB and as the parameter for vaccine efficacy evaluation has been understudied ( 49 ). However, B cells are observed in cattle infected with M. bovis , suggesting that antibodies may play a significant role in the control of mycobacterial infection ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, C. pseudotuberculosis can stimulate a variety of signaling pathways, such as the apoptosis and NF-κB signaling pathways [ 7 ]. Currently, the research on C. pseudotuberculosis has focused on the isolation and identification of the bacteria, molecular characterization and vaccine development [ 8 ]. However, the specific molecular mechanisms underlying the pathogenesis of a C. pseudotuberculosis infection are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the reduction in the cost of and the improvement of technology, high-throughput sequencing has been fully applied in modern agricultural research, mainly in the fields of crop breeding, livestock and poultry disease diagnosis and livestock and the improvement in the poultry breeding guidance, etc., gradually showing its application advantages [ 8 ]. Aboshady identified variants in the GIN-sensitive or GIN-resistant creole goat genome by RNA seq, and the T-cell receptor signaling pathway was one of the most important pathways to distinguish the resistant from the susceptible genotypes, with 78% of the genes in this pathway showing a genomic variation.…”
Section: Introductionmentioning
confidence: 99%